Fage Litik Spesifik Escherichia coli pada Limbah Cair Pasar Tradisional di Kota Banda Aceh - Iswadi Iswadi (Universitas Islam Negeri Ar-Raniry, 2016)
Changes in environmental conditions and behavior in patients taking antibiotics causes some pathogenic bacteria become resistant. Increased bacterial resistance to antibiotics encourages applications as biocontrol phage to reduce pathogenic bacteria. This research aims to detect lytic phage on liquid waste traditional market in lysizing Escherichia coli bacteria. Plaque assay method was used in detecting lytic phage in wastewater. The Phage assay results from samples of wastewater traditional markets in Banda Aceh showed that specific lytic phage of E. coli was not detected; it is shown by the absence of clear zone formation on double-layer media (plaque assay negative).